The Impact of Groundwater Utilization Permits in Environmental Legal Assessment - Dewi, Radna; Affila; Sukardi (TALENTA Publisher, Universitas Sumatera Utara, 2023)
The background of this research comes from the phenomenon that issuing groundwater utilization permits faces a few problems. First problem is public institutions or companies do not consider it important to get permits. Second problem is there is no research explaining how the permits relate with environmental law assessment. This study determines the impact of the issuing of groundwater utilization permits on environmental law and analyses the impact before and after receiving permits focusing on socio-economic, environment, and administrative aspects. Around 100 respondents from 100 institutions and companies in North Sumatera province are interviewed. For in-depth research we interview person in-charge of three different institutions Estomihi Medan Hospital, Grand Antares Hotel, and Bahagia Swimming Pool. By using SPSS software it shows that there is an impact of groundwater utilization permits on environmental law on the socio-economic and environmental aspects but not on the administrative aspect.